Association between wasting and food insecurity among children under five years: findings from Nepal demographic health survey 2016 - Sajama Nepali; Padam Simkhada; Ian Glynn Davies (BMC, 2020)
Abstract Background Wasting is a consequence of food insecurity, inappropriate dietary practices, and inadequate caring and feeding practices. The present study assessed association between wasting and household food insecurity among under 5 years old children, along with other socio-demographic characteristics. Methods This study is a secondary analysis of the Nepal Demographic and Health Survey 2016. The survey is cross-sectional in design with use of standardized tools. The sampling frame used is an updated version of the frame from the 2011 National Population and Housing Census. The participants were children under 5 years of age (n = 2414). Logistic regression was carried out to identify the odds of being wasted for children belonging to different levels of food insecure households using odds ratio and 95% confidence intervals. Results The prevalence of wasting increased with the level of food insecurity, from mild (9.4%) to moderate (10.8%) and to severe (11.3%). The highest proportions of wasted children were in Province 2 (14.3%), from rural areas (10.1%), born to mothers with no education (12.4%) and from a richer quintile (11.3%). Children belonging to severe food insecure households had 1.36 (95%CI 0.72-2.57) adjusted odds of being wasted and those belonging to mild food insecure and moderately food insecure households had 0.98 (95%CI 0.64-1.49) and 1.13 (95%CI 0.65-1.97) odds of being wasted respectively. Province 1 (AOR 2.06, 95%CI 1.01-4.19) and Province 2 (AOR 2.45, 95%CI 1.22-4.95) were significantly associated with wasting. Conclusion Considering the increment in childhood wasting as per level of food insecurity, an integrated intervention should be developed in Nepal that, 1. addresses improving knowledge and behavior of community people with respect to diet and nutrition; 2. reduce the problem of food insecurity through agricultural interventions.